Attitudes and Skills of the Counselor - the Field of Psychology - Neaga, Susanu (New Trends in Psychology, 2022)
The counselor’s personality represents the essential tool of the intervention, being the default model for managing problematic life situations. The counselor’s values cannot be consciously expressed because they affect the self-evaluation process necessary for the “individuation” of the client. The theoretical-technical analysis and synthesis is done through the personality of the counselor who “builds” the client’s reality. The counselor’s personality is the essential framework element, the filter, and the integrative factor of the counselor’s technical-theoretical ensemble. Attitude expresses a way of relating to certain affective, cognitive and behavioral aspects and implications. Empathy - one of the secrets of effective communication is the ability to put yourself in the situation of the person in front of you and understand his way of seeing things.